2017
DOI: 10.1016/j.agwat.2016.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of saline reclaimed waters and deficit irrigation on Citrus physiology assessed by UAV remote sensing

Abstract: • Reclaimed water significantly reduced total chlorophyll in grapefruit and mandarin leaves. • Normalized Difference Vegetation Index (NDVI) was related to gas exchange variations. • Near infrared (NIR) and red (R) domains were the best spectral indicators for both species. • Usefulness of remote sensing for assessing diurnal changes in Citrus physiology was confirmed. Effects of saline reclaimed waters and deficit irrigation on Citrus physiology assessed by UAV remote sensing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 60 publications
3
52
0
1
Order By: Relevance
“…Crops reflectance properties convey information about the crop, for instance, a healthier crop has higher reflectance in the NIR band. Most often, the bands are mathematically combined to form VIs, which provide information on the crop's health, growth stage, biophysical properties, leaf biochemistry, and water stress [29,[215][216][217][218]. Using multispectral or hyperspectral data, several Vis, such as green normalised difference vegetation index (GNDVI), renormalised difference vegetation index (RDVI), optimized soil-adjusted vegetation index (OSAVI), transformed chlorophyll absorption in reflectance index (TCARI), and TCARI/OSAVI, amongst others [34,79,82], can be calculated that correlate with the water stress of horticultural crops (see Table 2).…”
Section: Spectral Indicesmentioning
confidence: 99%
“…Crops reflectance properties convey information about the crop, for instance, a healthier crop has higher reflectance in the NIR band. Most often, the bands are mathematically combined to form VIs, which provide information on the crop's health, growth stage, biophysical properties, leaf biochemistry, and water stress [29,[215][216][217][218]. Using multispectral or hyperspectral data, several Vis, such as green normalised difference vegetation index (GNDVI), renormalised difference vegetation index (RDVI), optimized soil-adjusted vegetation index (OSAVI), transformed chlorophyll absorption in reflectance index (TCARI), and TCARI/OSAVI, amongst others [34,79,82], can be calculated that correlate with the water stress of horticultural crops (see Table 2).…”
Section: Spectral Indicesmentioning
confidence: 99%
“…Ivushkin et al [35] have tried combining a WIRIS thermal camera, a Rikola hyperspectral camera and a Riegl VUX-SYS LiDAR scanner to measure salt stress in quinoa plants, and they found UAV-borne remote sensing to be a useful technique for salt stress measurements. Romero-Trigueros et al [36] concluded that the red and near-infrared bands were critical to assess the saline stress Citrus suffered from. However, no existing literature has discussed the potential of synthesizing UAV-borne hyperspectral data and EMI measurements for soil salinity estimation.…”
Section: Introductionmentioning
confidence: 99%
“…Hal ini dikarenakan pemanfaatan penginderaan jauh memberikan banyak keuntungan dan kemudahan untuk menganalisis berbagai hal. Pemanfaatan metode penginderaan jauh untuk bidang kebumian, semakin berkembang pesat dengan adanya teknologi Unmanned Aerial Vehicle (UAV) (Trigueros et al, 2017;Maulana dan Wulan, 2015a;Bemis et al, 2014).…”
Section: Pendahuluanunclassified